PENGARUH TRANSPARANSI, PEMAHAMAN, PERSEPSI KEADILAN, DAN KEPERCAYAAN PADA PEMERINTAH TERHADAP KEPATUHAN CALON WAJIB PAJAK - Miranda Bilqis Nabilarozan; Lilik Pirmaningsih (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The purpose of this study is to test the influence of Tax Transparency, Tax Understanding, Perception of Tax Fairness, and Trust in the Government on Prospective Taxpayer Tax Compliance. Using a quantitative approach, this study focuses on Accounting students of Wijaya Kusuma University Surabaya (UWKS) as the research population. Sample selection used a purposive sampling method, yielding 100 respondents, and data were analyzed using multiple linear regression. The results of the simultaneous test indicate that all independent variables influence student tax compliance. However, the partial analysis reveals that only Tax Transparency and Tax Understanding have a significant influence on Prospective Taxpayer Compliance. In contrast, Perception of Tax Fairness and Trust in the Government show no significant influence.